2020
DOI: 10.1016/s2666-5247(20)30120-8
|View full text |Cite
|
Sign up to set email alerts
|

Humoral response and PCR positivity in patients with COVID-19 in the New York City region, USA: an observational study

Abstract: Background Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic. The proportion of infected individuals who seroconvert is still an open question. In addition, it has been shown in some individuals that viral genome can be detected up to 3 months after symptom resolution. We investigated both seroconversion and PCR positivity in a large cohort of convalescent serum donors in the New York City (NY, USA) region. Methods In this observa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
170
7
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(198 citation statements)
references
References 21 publications
19
170
7
2
Order By: Relevance
“…3, B and C ). Unexpectedly, but in agreement with earlier observations that seroconversion in mild COVID-19 cases might take a longer time to mount ( 8 ), we saw an increase in individuals who had an initial titer of 1:320, 1:160, or 1:80 ( Fig. 3, D to F ) from day 30 to day 82.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…3, B and C ). Unexpectedly, but in agreement with earlier observations that seroconversion in mild COVID-19 cases might take a longer time to mount ( 8 ), we saw an increase in individuals who had an initial titer of 1:320, 1:160, or 1:80 ( Fig. 3, D to F ) from day 30 to day 82.…”
supporting
confidence: 92%
“…Therefore, the assay used in this study to characterize the antibody response to SARS-CoV-2 is based on the trimerized, stabilized ectodomain of the spike protein (7). An enzyme-linked immunosorbent assay (ELISA) initially developed in early 2020 has been extensively used in research (7)(8)(9)(10). The so-called Mount Sinai ELISA has high sensitivity (92.5%) and specificity (100%) as determined with an initial validation panel of samples (table S1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In both saliva and serum, IgG appeared before or at approximately the same time as IgM, consistent with the stimulation of preexisting, cross-reactive B cells. Both synchronous and classical antibody isotype responses have been reported following SARS-CoV-2 infection ( 18 21 ). The sensitivity of our assay improved overall when convalescent-phase samples (≥10 DPSO) compared to acute-phase samples (<10 DPSO) were used for all SARS-CoV-2-specific antibody isotypes.…”
Section: Discussionmentioning
confidence: 99%
“…That testing was performed by individuals trained in oropharyngeal swab techniques and during follow-up, no additional staff members became symptomatic would suggest initial case detection was complete. We recognize that some individuals may not develop antibodies to SARS-CoV-2, however, seroconversion has recently been reported to be as high as 99% for patients if follow-up is extended beyond 15 days from symptom onset ( Wajnberg et al , 2020 ). In keeping with this, a recent systematic review and meta-analysis of antibody test performance, derived from 54 study cohorts with 15 976 samples, reported antibody tests had a sensitivity of 30.1% (95% CI 21.4 to 40.7) for 1 to 7 days, 72.2% (95% CI 63.5 to 79.5) for 8 to 14 days and 91.4% (95% CI 87.0 to 94.4) for 15 to 21 days after the onset of symptoms ( Deeks et al , 2020 ).…”
Section: Discussionmentioning
confidence: 99%